2015
DOI: 10.1007/s10517-015-2816-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers of Arterial Hypertension in Patients with Normotony, Pre-Hypertension and Hypertension

Abstract: We studied concentrations of angiotensin II, HLDF24 peptide, endothelin proteins, S100B, and autoantibodies to them and serum levels of blood natriuretic peptide in patients with different categories of "normal" arterial BP and hypertension. The relationship between blood levels of the above factors and normotony, pre-hypertension, and hypertension in the examined groups was analyzed. The results suggest that the studied molecular factors can serve as potential predictors of arterial hypertension and used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…Having considered all the above, and in agreement with recent literature [24,25], it seems that hypertension may be attributed to autoimmunity. It is well known that hypertension is prevalent in autoimmune disease and is an early symptom of the following renal involvement.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Having considered all the above, and in agreement with recent literature [24,25], it seems that hypertension may be attributed to autoimmunity. It is well known that hypertension is prevalent in autoimmune disease and is an early symptom of the following renal involvement.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, we excluded patients with thrombotic events, which may be a clinical manifestation of APS. Moreover, in this study we do not measure other autoantibodies such as anti-Angiotensin II, anti-atrial natriuretic peptide or gene polymorphisms which may play role in the pathogenesis of hypertension [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the use of S100B protein as a TBI trauma biomarker, recent studies also indicate other possible applications. This protein can also be used as a predictor of hypertension 18 ; however, in our cohort, no correlation between S100B protein and hypertension was proven. Current knowledge of the S100B protein and its uses is beyond the scope of this communication.…”
Section: Discussioncontrasting
confidence: 70%
“…9 Further, Sherstnev et al have indicated that serum levels of S100B can be used as possible predictors of arterial hypertension. 32 Possibly, increased S100B level in hypertensive patients is an adaptive response to catecholamines enhancement in these subjects. 33,34 It has been reported that catecholamine injection induces S100B mRNA and protein in myocardial tissue, ventricular myocytes and increased S100B in arterial tissues.…”
Section: Discussionmentioning
confidence: 99%